Magnetospheric sawtooth events during the solar cycle 23. Issue 10 (22nd October 2013) - Cai, X.; Clauer, C. R.
<x xml:space="preserve">Abstract</x> [1] The Earth's magnetosphere and ionosphere have a variety of responses to different solar activities. As a result, there are several types of magnetosphere response modes; one of which is termed sawtooth injection events. Currently, it is still unclear whether sawtooth events occurrence has a solar cycle dependence. Partially, this is due to a lack of an event list which covers a full solar cycle. In this research, we have extended our original event list to cover the solar cycle 23, which now includes 126 events from 1996 to 2007. Sawtooth events have been grouped into three categories based on their solar wind drivers: interplanetary coronal mass ejections, stream interaction regions, and others. Then we examine in detail whether sawtooth events occurrence has dependencies on solar cycle and season. We also test a hypothesis that sawtooth events occurrence is related to a threshold of total eroded magnetic flux at the magnetopause regardless of solar wind structures. This paper suggests understanding sawtooth events and other convection modes from solar wind magnetic flux or energy aspect rather than from structure aspect, which is an important idea to understand the complicated magnetosphere dynamics.